Xenopus Pkdcc1 and Pkdcc2 are two new tyrosine kinases involved in the regulation of JNK dependent Wnt/PCP signaling pathway - Vitorino, Marta; Silva, Ana Cristina; Inácio, José Manuel; Ramalho, José Silva; Gur, Michal; Fainsod, Abraham; Steinbeisser, Herbert; Belo, José António (PLOS ONE, 2015)
Protein Kinase Domain Containing, Cytoplasmic (PKDCC) is a protein kinase which has been implicated in longitudinal bone growth through regulation of chondrocytes formation. Nevertheless, the mechanism by which this occurs remains unknown. Here, we identified two new members of the PKDCC family, Pkdcc1 and Pkdcc2 from Xenopus laevis. Interestingly, our knockdown experiments revealed that these two proteins are both involved on blastopore and neural tube closure during gastrula and neurula stages, respectively. In vertebrates, tissue polarity and cell movement observed during gastrulation and neural tube closure are controlled by Wnt/Planar Cell Polarity (PCP) molecular pathway. Our results showed that Pkdcc1 and Pkdcc2 promote the recruitment of Dvl to the plasma membrane. But surprisingly, they revealed different roles in the induction of a luciferase reporter under the control of Atf2 promoter. While Pkdcc1 induces Atf2 expression, Pkdcc2 does not, and furthermore inhibits its normal induction by Wnt11 and Wnt5a. Altogether our data show, for the first time, that members of the PKDCC family are involved in the regulation of JNK dependent Wnt/PCP signaling pathway.